2012
DOI: 10.1007/s10517-012-1912-4
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Lipid Peroxidation in Infertile Women from Different Populations

Abstract: We studied parameters of lipid peroxidation (LPO) in women with infertility, resident of the Republic of Buryatia. The levels of malonic dialdehyde (MDA) were increased in the examined infertile women from Buryat and Russian populations. Reduced total antioxidant activity, activity of superoxide dismutase (SOD), and α-tocopherol levels were revealed in patients from Buryat population; decreased concentrations of reduced glutathione were recorded in patients from Russian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 2 publications
0
9
0
5
Order By: Relevance
“…При об-следовании женщин с ýндокринным бесплодием бурятской и русской ýтногрупп установлено, что в целом у обследованных пациенток происходит увеличение содержания конечных (ТБК-актив-ных) продуктов ПОЛ. При ýтом у пациенток бу-рятской ýтногруппы отмечается снижение общей АОА, активности СОД и уровня α-токоферола, у женщин русской ýтногруппы -дисбаланс в си-стеме глутатиона [81]. Распределение генотипов и аллелей гена детоксикации GSTP1 у обследован-ных русских женщин с наружным генитальным ýндометриозом (НГЭ) и бесплодием характеризо-валось повышением частоты «мутантного» аллеля В гена детоксикации GSTP1, что не характерно для буряток с НГЭ и бесплодием.…”
Section: обзоры и лекцииunclassified
“…При об-следовании женщин с ýндокринным бесплодием бурятской и русской ýтногрупп установлено, что в целом у обследованных пациенток происходит увеличение содержания конечных (ТБК-актив-ных) продуктов ПОЛ. При ýтом у пациенток бу-рятской ýтногруппы отмечается снижение общей АОА, активности СОД и уровня α-токоферола, у женщин русской ýтногруппы -дисбаланс в си-стеме глутатиона [81]. Распределение генотипов и аллелей гена детоксикации GSTP1 у обследован-ных русских женщин с наружным генитальным ýндометриозом (НГЭ) и бесплодием характеризо-валось повышением частоты «мутантного» аллеля В гена детоксикации GSTP1, что не характерно для буряток с НГЭ и бесплодием.…”
Section: обзоры и лекцииunclassified
“…There is decomposition of unsaturated fatty acids and the decrease of protein composition in cell membranes at the deficiency of vitamin E [4]. Moreover, ␣-tocopherol impacts on various links of the reproductive system and stimulate steroidogenesis in ovary, protein biosynthesis in endometrium, and other target organ of steroid hormone [27] and its deficiency has pathogenetic significance for development of the reproductive system disorders in women [7][8][9]. Published data, which have shown age aspects of the content ␣-tocopherol in women are ambiguous [10][11][12][13] but our data are consistent with results in which was showed the decrease of the ␣-tocopherol level in postmenopausal woman [10,11].…”
Section: Parametersmentioning
confidence: 99%
“…There is a powerful system of the antioxidant defense for neutralization free radicals in a body, which includes enzymes (superoxide dismutase, catalase, glutation peroxidase, glutation-S-transferase, glutation reductase) and non-enzymatic antioxidants (tocoferol, retinol, glutation, ascorbic acid, melatonin, and etc.). Recent data have shown that the antioxidant deficiency can play an important role in the development of reproductive system dysfunction in women [7][8][9]. The studies on age-related changes of antioxidant system parameters in women during various climacteric periods and their effect on emergence of different disorders arouse great interest at present time [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The production of endogenous antioxidants such as GSH, is considered an alternative to combat these oxidative damage caused by ROS, given that it helps neutralize and repair the damage caused by oxidative stress (Ribeiro et al, 2005). Recent data have been showing that the efficiency in this antioxidant system can play an important role in the development of dysfunctions of the female reproductive system (Miquel et al, 2006;Kolesnikova et al, 2012). In this context, the infusion of lemon grass on 50 g/L demonstrated an important antioxidant effect, viewing that, in just one hour of treatment in water bath on 37 o C the plant increased the GSH levels in the concentration of 50 g/L, what possibly would be favorable to the decreasing of the protein and lipid damages generated in the period of post-menopause in case that the period of contact of the erythrocytes to the infusion were bigger (Figure 3).…”
Section: Resultsmentioning
confidence: 99%